ANALYSIS OF TRAINING AND CAREER DEVELOPMENT ON NON-ASN PERFORMANCE ASSESSMENT WITH COMPETENCE AS A MODERATING VARIABLE MEDAN BARU DISTRICT - Reni Sihombing; M. Chaerul Rizky; Kiki Farida Ferine (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of training and career development on the performance assessment of Non-Civil Servant (Non-ASN) employees in Medan Baru District, with competency as a moderating variable. This study was conducted to explore how much training and career development can influence the performance assessment of Non-ASN employees and how competency plays a role in strengthening the relationship between these variables. The method used in this study is quantitative with a Structural Equation Modeling (SEM) analysis approach using SmartPLS software. The sample of this study was 64 Non-ASN employees who are the population in Medan Baru District. The results of the study indicate that training has a positive and significant influence on the performance assessment of Non-ASN employees, as well as career development and competency which have a significant influence on performance assessment. Competence was also found to strengthen the relationship between training and performance assessment. However, career development does not have a significant effect on performance assessment that is strengthened by competency. This study provides an important contribution to human resource management in the public sector, particularly in the management of Non-ASN employees, by providing suggestions to improve the effectiveness of training and career development that are more relevant and focused on employee needs. It is hoped that the results of this study can strengthen human resource management policies in improving employee performance in the government sector.